Influence Health Promotion of Personal Protective Equipment to Increase Knowledge About Contact Dermatitis in Citrus Farmers in Cingkes Village Kabupaten Simalungun - Samuel Marganda Halomoan Manalu; Deli Syaputri; Nelson Tanjung; Riyanto Suprawihadi; Nurmala Hayati S (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Occupational Contact Dermatitis is a skin disorder that is often found in farmers who spray pesticides. Knowledge of the use of personal protective equipment on citrus farmers in Cingkes Village is still low, therefore it is very important to provide health counseling on the use of personal protective equipment on farmers. The purpose of the study was to determine the effect of health promotion about pesticides and the use of personal protective equipment on increasing knowledge about dermatitis in citrus farmers in Cingkes Village, Simalungun Regency. This type of research is quasi-experimental with a one group pre test-post test research design. This research was conducted in Cingkes Village, Simalungun Regency, which was carried out from July to September 2023. The research sampling was carried out by purposive sampling method. The instruments used were questionnaires and standing banners, leaflets and demonstrations on the use of personal protective equipment to improve farmers' knowledge of contact dermatitis. Data were analyzed using Wilcoxon signed rank test with SPSS version 20 software. The results showed that there is a significant influence of health promotion regarding Personal Protective Equipment on knowledge of contact dermatitis among orange farmers in Cingkes Village, Simalungun Regency (p-value=0.000). To the government and health workers to increase the knowledge of farmers by providing health counseling in order to prevent the occurrence of dermatitis in farmers. to citrus farmer farmers should use gloves, protective clothing, glasses, and masks when working with citrus or chemicals to prevent contact dermatitis. Keywords : Health Promotion, Dermatitis, Farmers, Knowledge, Personal Protective Equipment